Investigations of Glycol-ethanol Systems by Ultrasonic Method - KOTHAI, S. (Asian Journal of Chemistry, 2010)
Ultrasonic investigations have been employed to understand the polymer-solvent interactions in solutions. Glycol-solvent interaction has been investigated by ultrasonic method over a wide range of concentration at 303 K. The ultrasonic velocities (U), densities (ρ) and viscosities (η) are determined for ethanolic solutions of ethylene glycol (EG), diethylene glycol (DEG), triethylene glycol (TEG) at 303 K. The acoustical parameters are investigated for glycol-ethanol systems at 303 K.